2006
DOI: 10.1111/j.1742-481x.2006.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of stage I pressure ulcers and related factors

Abstract: The prognosis of stage I pressure ulcers cannot be predicted; therefore, nursing interventions for preventing their deterioration have not been clearly established. This study describes the clinical course of stage I pressure ulcers and prospectively investigates the factors related to their deterioration. Thirty-one stage I pressure ulcers in 30 patients in a long-term care facility were studied, and morphological changes were assessed every day until the ulcers healed or deteriorated. The physiological chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 11 publications
(12 reference statements)
1
38
1
Order By: Relevance
“…1,20 Therefore, vibration appears to hasten the healing period of Stage I PrUs. It has been reported that 35.5% of Stage I PrUs advance to Stage II or more, 1 and it takes a longer time to heal these PrUs (Stage II, 24.8 days; Stage III, 136.8 days; Stage IV, 223.5 days).…”
Section: Effects Of Vibration On the Healing Of Stage I Prusmentioning
confidence: 98%
See 1 more Smart Citation
“…1,20 Therefore, vibration appears to hasten the healing period of Stage I PrUs. It has been reported that 35.5% of Stage I PrUs advance to Stage II or more, 1 and it takes a longer time to heal these PrUs (Stage II, 24.8 days; Stage III, 136.8 days; Stage IV, 223.5 days).…”
Section: Effects Of Vibration On the Healing Of Stage I Prusmentioning
confidence: 98%
“…It has been found that 35.5% of Stage I PrUs advance to Stage II or greater (National Pressure Ulcer Advisory Panel classification). 1 Therefore, it is important to provide appropriate care to prevent this progression.…”
Section: Introductionmentioning
confidence: 99%
“…Eligible patients had HAPUs of stages I through IV, unstageable HAPUs, or SDTI HAPUs develop between November 1, 2007, and May 31,2008. Eligible patients were identified by using the pressure ulcer database, which is described in more detail later.…”
Section: Setting and Patientsmentioning
confidence: 99%
“…(Critical Care Nurse. 2011;31 [4]: [30][31][32][33][34][35][36][37][38][39][40][41][42][43] 2008, the Centers for Medicare and Medicaid Services implemented a 0% complication rate for a number of clinical diagnoses, one of which is a stage III or IV pressure ulcer acquired during a hospitalization. 12 Consequently, hospitals are not reimbursed for the care, services, or resources associated with such a HAPU.…”
Section: Risk Profile Characteristics Associated With Outcomes Of Hosmentioning
confidence: 99%
“…The advanced PU management protocol was therefore effective in preventing PU deterioration at this early stage. Sato et al 31 reported that stage I PUs took 3 weeks to develop and increase in severity. Early detection and intervention for DTI substantially reduces the time required for healing.…”
Section: Discussionmentioning
confidence: 99%